Avaliação da taxa de filtração e alterações metabólicas em Limnoperna fortunei (Dunker, 1857) na presença de algas verdes e cianobactérias - Luiza de Oliveira Hudson (2014)
Limnoperna fortunei is a freshwater filter-feeding mussel native to Southeast Asia that was introduced to South America by ballast water in merchant ships. It was discovered in Argentina in 1991, at Rio de la Plata estuary. Since then, it can be found in many Brazilian waterbodies. Very similar to the bivalve Dreissena polymorpha, an invasive mussel from North America and Europe, both present planktonic larvae, early sexual maturity, high fecundity and wide environmental tolerance. Those characteristics allow them to overcome the transitions to be a successful invader into the new environment. They are excellent filter-feeders capable to reduce the fitoplankton biomass in watersystems and to enrich the substrate by the production of pseudofeces. Beside environmental problems they can cause economic losses because of their gregarious behavior, like the obstruction of pipes in industries and power plants. Cyanobacteria are also a constant problem in lakes and reservoir, which became eutrophic due to intense human activities. This study aimed to estimate L. fortunei filtration rates in the presence of some green algae, Chlorella sp, Ankistrodesmus sp. and Chlamydomonas sp, and the cyanobacteria, Microcystis aeruginosa, toxic and non-toxic strains, and Anabaena sp. The results showed that the golden mussel was capable of filtering M. aeruginosa at rates similar to the green algae. On the other hand, filtration rates were lower when feeding on Anabaena sp. Strains, maybe because Anabaena has a filamentous morphology and may produce saxitoxins. During a long term feeding experiment (24 days) on Microcystis, the concentration of calcium and glycogen were analyzed in L. fortunei. The calcium values present in the mussel´s shell were not different among experimental treatments. The glycogen concentration was lower in the starved group, as expected, but in the group feeding on M. aeruginosa, glycogen was similar to the control group. The results showed that toxic cyanobacteria when offered as a food with intact cells are easily ingested by adults of zebra mussel. Some physiologic parameters were also not affected by the toxin, showing the resistance of L. fortunei to cyanotoxins, as it was already been shown by others authors for D. polymorpha.